The Use of Derivatives to Hedge Embedded Options : The Case of Pension Institutions in Denmark - Ladekarl, Jeppe; Ladekarl, Regitze; Andersen, Erik Brink; Vittas, Dimitri (World Bank, Washington, DC, 2012)
The main purpose of this paper is to examine the growing use of derivatives by Danish pension institutions as a risk management tool to hedge embedded options on their balance sheets. Throughout the 1980s and 1990s it was a widespread practice for Danish pension institutions to guarantee a minimum interest rate on new pension policies. With the new millennium global interest rates declined steeply and equity markets came crashing down. Suddenly the guarantees on pension contracts were in the money. The policies already written could not be changed, leaving liabilities and assets mismatched, profits in the red, and capital reserves drained. Out of necessity, and in some cases virtue, Danish pension institutions turned in scale to derivatives, allowing for a more active approach to hedging, asset and liability management, and even profit generation. Through the use of derivatives, pension institutions have avoided the need to renegotiate their guaranteed contracts with policy holders. They have succeeded as an industry in transforming their pay-off curves and have emerged with better matched asset/liability positions and lower exposure to interest rate risk. But the expanded use of derivatives also raises some risk management and regulatory issues, such as operational and counterparty risks as well as effective internal control systems and regulatory oversight.